Radioprotective Agents in Radiotherapy: An Overview - Sridevi, Ugrappa; Jain, Ajay (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Cancer stands as one of the most common causes for death of the individual worldwide. Radiotherapy is one of the treatment modalities in cancer where, exposure of the normal tissue to these ionizing radiations, results in mutagenesis and cell death. Several modalities and clinical approaches have been made to reduce these early and late complications of the radiotherapies and one among them is, by the means of pharmacological agents. Many experimental and clinical studies have given rise to new concepts of chemical and molecular pharmacological agents as Radioprotective agents. These have been used to prevent damage to the tissues from the radiations that have been produced while diagnostic and treatment phases of carcinomas. To reduce the significant complications in irradiated patients, the clinical implication of these radioprotective agents have emerged as potential drugs and with anti-tumour effect in the radiotherapy of various cancers including oral carcinomas.